Hibernation for space travel: Impact on radioprotection. (November 2016) - Cerri, Matteo; Tinganelli, Walter; Negrini, Matteo; Helm, Alexander; Scifoni, Emanuele; Tommasino, Francesco; Sioli, Maximiliano; Zoccoli, Antonio; Durante, Marco
Abstract: Hibernation is a state of reduced metabolic activity used by some animals to survive in harsh environmental conditions. The idea of exploiting hibernation for space exploration has been proposed many years ago, but in recent years it is becoming more realistic, thanks to the introduction of specific methods to induce hibernation-like conditions (synthetic torpor) in non-hibernating animals. In addition to the expected advantages in long-term exploratory-class missions in terms of resource consumptions, aging, and psychology, hibernation may provide protection from cosmic radiation damage to the crew. Data from over half century ago in animal models suggest indeed that radiation effects are reduced during hibernation. We will review the mechanisms of increased radioprotection in hibernation, and discuss possible impact on human space exploration.